Response of Relativistic Electron Microbursts to the Arrival of High‐Speed Solar Wind Streams and its Relation to Flux Variation of Trapped Radiation Belt Electrons. Issue 9 (15th September 2018) - Kurita, S.; Miyoshi, Y.; Blake, J. B.; Friedel, R. H. W.
Abstract: Relativistic electron microbursts are frequently observed during high‐speed solar wind stream (HSS) events. However, solar wind parameters, which are important for enhanced microburst precipitation, have not been well understood. We perform a superposed epoch analysis of microburst occurrence frequency during HSS events, considering the north/south component of the interplanetary magnetic field (IMF Bz) and solar wind speed. The IMF Bz dependence is investigated considering the Russell‐McPherron effect following the method used by Miyoshi and Kataoka (2008, https://doi.org/10.1029/2007JA012506 ). We find that microbursts are most frequently observed during faster (>500 km/s) solar wind speed streams with the IMF Bz shifted southward (fast SBZ‐HSS events), indicating that both fast solar wind speed and the southward IMF Bz are important for enhanced microburst precipitation. The occurrence frequency of chorus waves during the HSS events is investigated to gain an understanding of the different behavior of microburst activity in response to the HSS events. We show that relativistic electron microbursts are not always a good proxy for chorus waves, but a proxy for a subset of chorus that can resonate with MeV electrons. We also show that electron fluxes with energies from hundreds of keV to several MeV preferentially increase during the fast SBZ‐HSS events. These results indicate that observation of an enhanced occurrence of relativistic electron microbursts could be used as a proxy for the direct observation of the acceleration of MeV electrons by chorus waves in the heart of the outer radiation belt, not just a proxy for chorus wave activity in general. Key Points: MeV electron microburst occurrence frequency strongly depends on both solar wind speed and the IMF Bz in HSS events MeV electron fluxes in the outer radiation belt are substantially enhanced during enhanced activity of MeV electron microbursts MeV electron microburst activity can be a proxy for MeV electron acceleration by chorus, not just a proxy for chorus activity in general